Effect of Different Extraction Methods and Geographical Origins on the Total Phenolic Yield, Composition, and Antimicrobial Activity of Sugarcane Bagasse Extracts - Velázquez-Martínez, Victor; Valles-Rosales, Delia; Rodríguez-Uribe, Laura; Laguna-Camacho, Juan Rodrigo; López-Calderón, Hector Daniel; Delgado, Efren (Frontiers in Nutrition, 2022)
Several parameters including particle size, solvent, temperature, and extraction method affect the extraction yield of phenolic compounds from a plant matrix. Considering the wide availability of sugarcane bagasse, this study analyzed the effect of different extraction methods as well as geographical origins on the yield, quality, and antimicrobial activity of phenolic compounds from sugarcane bagasse extracts. Samples from three geographical locations (Veracruz, Mexico; Santa Rosa, Texas, USA; and St. Mary, Louisiana, USA) were analyzed. The antimicrobial activity of the extracted bioactive compounds was also investigated. Extraction was performed using an orbital shaker or ultrasonic bath for various times at a fixed temperature of 50 °C, with 90% ethanol or methanol. The highest yield (5.91 mg GAE) was obtained using an orbital shaker for 24 h with 90% methanol as the solvent. HPLC-MS identified desferrioxamine b, baicalein, madecassic acid, and podototarin at different concentrations in all three sugarcane bagasse samples. The antimicrobial activity of these compounds was tested against Escherichia coli K12, Bacillus cereus, Enterobacter aerogenes, Streptococcus aureus, and E. cloacae as well as with modified yeasts MLH1, SGS1, MGT1, and RAD14, carrying mutations related to different cancer types. In addition, the results were compared with the Effect of ampicillin and kanamycin. The sugarcane bagasse extracts showed up to 90% growth inhibition against B. cereus at 200–800 µg/mL and 50% growth inhibition against S. aureus at 800 µg/mL. The inhibitory effect against modified yeast SGS1, RAD14, and MLH1 was 50–80% at 800 µg/mL. The percentage of inhibition and the phenolic compound contents differed depending on the origin of the sugarcane bagasse sample. These findings are promising for using this industrial byproduct to obtain compounds for nutraceutical, food additive, or medical uses.